The Correlation between Reasoning and Emotional Intelligence in Social Interaction to Mathematics Achievement - Dafid Slamet Setiana; Nuryadi Nuryadi; Rusgianto Heri Santoso (Hipotenusa : Journal of Mathematical Society, 2020)
The objective of the research was to determine the correlation between reasoning, and emotional intelligence in social interaction to mathematics achievement. The research was conducted at SMP 5 Yogyakarta, Indonesia with 90 respondents who were selected by random sampling. The research verified the hypothesis used a survey method with correlation and regression technique approach. The research involved 3 (three) variables such as; mathematics achievement as the dependent variable and two other variables as the independent variables. They were reasoning and emotional intelligence in social interaction. The study found that there was a positive correlation between (a) reasoning and mathematics achievement; (b) emotional intelligence in social interaction and mathematics achievement; and (c) there was a positive correlation between reasoning and emotional intelligence in the social interaction to mathematics achievement. This study is expected to be a consideration for developing mathematical achievement through student reasoning, developing mathematical achievement through emotional intelligence in social interactions, and developing mathematical achievement through reasoning and emotional intelligence in social interactions.